2021
DOI: 10.1007/s00405-021-06626-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional results after implantation of the bonebridge, a semi-implantable, active transcutaneous bone conduction device, in children and adults

Abstract: Purpose Aim of the study was to evaluate the surgical, clinical and audiological outcome of 32 implantations of the Bonebridge, a semi-implantable transcutaneous active bone conduction implant. Methods In a retrospective cohort study, we analyzed data for 32 implantations in 31 patients (one bilateral case; seven age < 16 years) with conductive or mixed hearing loss, malformations, after multiple ear surgery, or with single-sided deafness as contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 37 publications
2
24
0
3
Order By: Relevance
“…Regarding the occurrence and treatment of major complications, in the present review, a complication rate of 5.7% was observed for BoneBridge, which is in agreement with literature studies, such as that by Brkic (2020), in which the rate of major complications with the use of BoneBridge was 9.4% (6/64), including 5 explantations and 1 reimplantation. 19 Similar results were also found in the study by Seiwerth (2021), 27 in which the major complication rate was 6.2%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the occurrence and treatment of major complications, in the present review, a complication rate of 5.7% was observed for BoneBridge, which is in agreement with literature studies, such as that by Brkic (2020), in which the rate of major complications with the use of BoneBridge was 9.4% (6/64), including 5 explantations and 1 reimplantation. 19 Similar results were also found in the study by Seiwerth (2021), 27 in which the major complication rate was 6.2%.…”
Section: Discussionsupporting
confidence: 84%
“…Transcutaneous devices generally show a significant reduction in patient injuries when compared with percutaneous models. 4 19 20 27 28 29 30 31 32 …”
Section: Discussionmentioning
confidence: 99%
“…Zernotti et al investigated 14 congenital atresia patients implanted with the, at the time only available, active BCI601 and reported significant improvements in hearing thresholds and word recognition scores accompanied with low complication rates. Magele et al reported from six studies in their meta-analysis on children with CHL or MHL an average FG of 34 dB [8,[24][25][26]. Especially, the sound localization ability, which was investigated with white noise presented at a level of 40 dB SPL from randomized angles of − 90°, − 45°, 0°, 45°, or 90° showed very pleasing results for both the testet cohort of CHL cases.…”
Section: Discussionmentioning
confidence: 99%
“…The processor has 16-band digital equalizer, 16 independent compression channels, sound smoothing, speech and noise management, adaptive directional microphones, intelligent sound adapter, classifier 5 different programs, wind noise reduction, ambient sound, speech cracking, omnidirectional microphones, audio frequency range 250-8 kHz, wireless connectivity options via Bluetooth or telecoil to external devices such as mobile phones, and FM-systems. The processor is powered, There are many studies in the literature showing the effectiveness of the BCI 601 implant, and the device can provide improved hearing in both children and adults [8,[11][12][13][14][15][16][17][18]. The primary aim of this study is to evaluate the effectiveness of the Bonebridge BCI 602 implant in a group of adult patients with conductive or mixed hearing losses.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the literature showing the effectiveness of the BCI 601 implant, and the device can provide improved hearing in both children and adults [ 8 , 11 18 ]. The primary aim of this study is to evaluate the effectiveness of the Bonebridge BCI 602 implant in a group of adult patients with conductive or mixed hearing losses.…”
Section: Introductionmentioning
confidence: 99%